Rural landholder judgements about the acceptability of cropping or draining wetlands on private land. Issue 1 (2nd January 2019) - Mendham, Emily; Curtis, Allan
ABSTRACT: Some landholders who have cropping enterprises utilise wetlands on their properties, even where such actions are unlawful. The ecological impacts of cropping or draining these environmental assets will vary, but the outcomes can be dramatic and irreversible. This article examines the judgements of rural landholders about the acceptability of cropping or draining wetlands. Data were gathered through a survey of rural landholders in western Victoria. Rural landholders were more likely to judge cropping or draining wetlands to be unacceptable than acceptable. Respondents who found these practices acceptable were more likely to have a business orientation and be farmers by occupation. Almost a third of respondents indicated they were 'unsure', suggesting there is an opportunity to influence their attitudes. However, the 'unsure' were more similar to those who found cropping or draining wetlands acceptable. Economic opportunities provided by these practices are an important barrier to conservation efforts. We suggest that management agencies target landholders with wetlands and offer financial incentives for their active management beyond that required by law, and provide learning opportunities around wetlands. It may also be necessary to more actively monitor and prosecute illegal activity to complement the existing focus on extension and cost sharing for on-ground work.